2021
DOI: 10.3389/fphar.2021.724725
|View full text |Cite
|
Sign up to set email alerts
|

Current Molecular Therapeutic Agents and Drug Candidates for Mycobacterium abscessus

Abstract: Mycobacterium abscessus has been recognised as a dreadful respiratory pathogen among the non-tuberculous mycobacteria (NTM) because of misdiagnosis, prolonged therapy with poor treatment outcomes and a high cost. This pathogen also shows extremely high antimicrobial resistance against current antibiotics, including the anti-tuberculosis agents. Therefore, current chemotherapies require a long curative period and the clinical outcomes are not satisfactory. Thus, there is an urgent need for discovering and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 171 publications
(234 reference statements)
0
28
0
Order By: Relevance
“…Because of the scarcity of literature on M. senegalense , we draw on treatment guidelines for NTM infections ( 14 , 15 ). From the literature review, we found that the management of NTM infections is quite difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the scarcity of literature on M. senegalense , we draw on treatment guidelines for NTM infections ( 14 , 15 ). From the literature review, we found that the management of NTM infections is quite difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Although, Mab subsp. massiliense isolates contain a truncated erm (41) gene that has shown improved clinical treatment outcomes ( Bronson et al, 2021 ; Quang and Jang, 2021 ). Furthermore, CLA treatment induces the expression of transcriptional regulator WhiB7, which causes upregulation of erm (41) and eis 2 (which provides AMK resistance) ( Pryjma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although these outcomes that were from currently recommended regimens look atrocious, there is no viable alternative because of no potent anti- Mab candidates that were approved its efficacy in humans through clinical trials. In this perspective, it is clear that there is an urgent need for discovering and developing novel, more innovative anti- Mab drugs ( Quang and Jang, 2021 ). Therefore, there have been many attempts to find the best partner for CLA to improve treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterium abscessus (Mab) has been recognised as a challenging respiratory pathogen among the non-tuberculous mycobacteria (NTM), often associated with poor outcomes of therapy and a high cost incurred due to prolonged therapy [1]. Although its acquisition was thought to occur through environmental exposure (e.g.…”
Section: Introductionmentioning
confidence: 99%